Keabsahan Perkawinan Sejenis dalam Hukum Ketatanegaraan - Ega Permatadani; Achmad Hariri (Universitas Muhammadiyah Yogyakarta, 2023)
Same-sex marriage is currently the attention of the Indonesian people due to news and issues circulating on social media that spread quickly and become a hot topic among the people. Marriage itself in general can be interpreted as a sacred bond carried out by both parties (male-female). However, at this time there are some groups who hope to carry out this same-sex marriage or there are some groups who have carried out same-sex marriages and harm one other party without knowing the truth. The purpose of this study is to find out how legal a same-sex marriage is in Indonesia, as well as what consequences will be received if it violates the legal basis that already exists and applies in Indonesia. This study uses a normative juridical research method with a statute approach which refers to the concept of law as a rule and also uses legal doctrines which are then analyzed qualitatively and described in a descriptive form so that the subject matter is found in conformity with the normative provisions. The results of this study are that same-sex marriage cannot be carried out because it is not in accordance with existing legal rules and norms. The legality and legal consequences of same-sex marriage are clearly explained in the 1945 Constitution of the Republic of Indonesia, Law Number 23 of 2006 concerning Population Administration, Law Number 1 of 1974 concerning Marriage and the Criminal Code.